RESPONSE OF CARROT VARIETIES (Daucus carota. L) TO DIFFERENT NUTRIENT SOURCES AND THEIR COMBINATIONS - Pandey, Ashmita; Sharma, Prof. Dr. Moha Dutta (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
A field experiment was carried out from November 2014 to April 2015 in farmer’s field, Fulbari, Chitwan, Nepal to evaluate the response of carrot varieties to different nutrient sources and their combinations. The experiment was laid out in two factorial randomized complete block design with three replications. Factor A consisted of three varieties i.e. Nepadream (hybrid), New Kuroda and Early Nantes and factor B consisted of five nutrient sources: 1) 100% RDF (60:40:40 NPK kg ha-1 ), 2) 100% FYM @ 10 t ha-1, 3)50% RDF plus 50% FYM, 4) 50% RDF plus 50% vermicompost , and 5) 100% vermicompost @ 4t ha-1. Significant differences were observed between the performance of the three varieties (P<0.05). Results revealed that all vegetative attributes were higher in Nepadream at early growth stage, but at later stage it was lower than OP varieties. However, Nepadream produced significantly higher yield (28.56 t ha-1) than OP varieties. Comparing the nutrient treatments, independent on the varieties, all combinations of 50% RDF were found significantly effective in achieving better physio-morphological, growth attributes and yield and yield attributes as compared to their sole applications. The root yield obtained by 100% RDF (24.06 t ha-1), 50% RDF plus 50% FYM (24.68 t ha-1) and 50% RDF plus 50% vermicompost (25.28 t ha-1) were comparable. However application of 50% RDF along with 50% vermicompost performed best among all nutrient sources